The Influence of Technical Marketing Training toward International Trade Access at BP3ED Department of Commerce and Industry of South Sulasesi Province - Mariani Alimuddin; Gunawan B I; Abdul Razak Munir (Jurnal Mirai Management, 2016)
ABSTRACT The objectives of this research are: 1. To analyze the influence of Simultaneous export procedure, Letter of Credit (L/C) andTransportation training toward international trade. 2. To analyze the influence of Partial export training toward international trade access. 3. To analyze the influence of partial L/C training toward international trade access. 4. To analyze the influence of partial Transportation training toward international trade access. This research done at BP3ED Department of commerce and industry of South Sulawesi Province. This research used accidental sampling method with 71 training participant data analyze in this research used validity, reability and multiple linear regression analyze test processed by using SPSS 31. The results of this research, as follow: 1. Export procedure, L/C and transportation training gave positive and significant influence toward international trade access. 2. Export procedure training give positive and significant influence toward influence toward international trade access. 3. L/C training give positive influence, however it did not give significant influence on international trade access. 4. Transportation training give positive influence, however it did not give significant influence on international trade access. Key words: export, L/C, transportation, international trade.